The comparative economics of ICT, environmental degradation and inclusive human development in Sub-Saharan Africa - Simplice Asongu; Jacinta C. Nwachukwu; Chris Pyke (African Governance and Development Institute (AGDI), 2018)
This study examines how information and communication technology (ICT) could be employed to dampen the potentially damaging effects of environmental degradation in order to promote inclusive human development in a panel of 44 Sub-Saharan African countries. ICT is captured with internet and mobile phone penetration rates whereas environmental degradation is measured in terms of CO 2 emissions per capita and CO 2 intensity. The empirical evidence is based on Fixed Effects and Tobit regressions using data from 2000-2012. In order to increase the policy relevance of this study, the dataset is decomposed into fundamental characteristics of inclusive development and environmental degradation based on income levels (Low income versus (vs.) Middle income); legal origins (English Common law vs. French Civil law); religious domination (Christianity vs. Islam); openness to sea (Landlocked vs. Co astal); resource-wealth (Oil-rich vs. O il-poor) and political stability (Stable vs. Unstable). Baseline findings broadly show that improvement in both of measures of ICT would significantly diminish the possibly harmful effect of CO 2 emissions on inclusive human development. When the analysis is extended with the abovementioned fundamental characteristics, we observe that the moderating influence of both our ICT variables on CO 2 emissions is higher in the group of English Common law, Middle income and Oil-wealthy countries than in the French Civil law, Low income countries and Oil-poor countries respectively. Theoretical and practical policy implications are discussed.
Keywords: C52; O38; O40; O55; P37; 330; CO 2 emissions; ICT; Economic development; Africa